Intraoral Palatal Lipoma: A Rare Case Report - Gupta, Anuya Satyaprakash; Ghate, Girija Amit (Indian Journal of Case Reports, 2019)
Lipomas are the commonest occurring benign neoplasms of the human body originating from adipose cells. Intraoral lipomas are rare, contributing to less than 5% of all head and neck neoplasms. Even so, lipoma should be considered as a differential diagnosis in swellings of the oral cavity. Surgical excision is the mainstay of treatment in the case of intraoral lipoma. In this case report, the lipoma was seen originating from the soft palate. It was surgically excised in toto and was subjected to histopathological investigations to reach a definitive diagnosis. This case is being reported as it is uncommon for a lipoma to have an intraoral origin and even more rare for it to be seen occurring in the palate.